A single amino acid mutation alters multiple neutralization epitopes in the respiratory syncytial virus fusion glycoprotein - Ahmed K. Oraby; Aleksandra Stojic; Farah Elawar; Leanne M. Bilawchuk; Ryley D. McClelland; Kaci Erwin; Madison J. Granoski; Cameron D. Griffiths; Justin D. Frederick; Elena Arutyunova; M. Joanne Lemieux; Frederick. G. West; et al. (npj Viruses)
Abstract Respiratory syncytial virus (RSV) is the leading cause of infant hospitalization. All current RSV therapeutics, including antibody prophylaxis and adult vaccination, target the RSV fusion glycoprotein (RSV-F). The seven neutralization sites on RSV-F are highly conserved and infrequently mutate. Here, we show that a single amino acid mutation at position 305 in RSV-F significantly alters antigenic recognition of RSV-F binding sites and reduces the susceptibility of RSV to neutralizing antibodies. In an in vitro evolution assay, we show that RSV-F L305I occurs in a majority of RSV quasi-species. Computational modeling predicted that the L305I mutation altered the epitope landscape of RSV-F, resulting in changes to neutralizing antibody sensitivity and affinity towards the RSV-F glycoprotein. Screening of published RSV-F sequences revealed that position 305 in RSV-F was conserved with a leucine and isoleucine in RSV-A and RSV-B subtypes respectively. Our study suggests that select amino acids in RSV-F may act as ‘conformational switches’ for RSV to evade host serum antibodies. This work has important implications in understanding RSV evolution and resistance as it suggests that mutational resistance to neutralizing antibodies can occur at sites distal to antigenic epitopes, significantly altering antibody sensitivity to viral infection. These unique antigenic landscape changes should be considered in the context of vaccine and therapeutic development in order to better understand viral mechanisms of evasion and resistance.